Navigating seasonality in cotton-based farming systems in southern Mali - Arouna Dissa; Maja Slingerland; Ken E. Giller; Katrien Descheemaeker (Climate Risk Management)
Smallholder farmers’ livelihoods follow predictable and cyclical patterns related to annual cycles of weather, crop and animal production and market fluctuations. Understanding seasonality forms an essential part of unravelling farming systems behaviour and performance, especially in contexts with strong seasonality, such as southern Mali. Farmers make strategic, tactical and operational decisions related to different time horizons to support their agricultural activities. The diverse resource endowments of farming households influence their decisions, and adaptive capacity. This study aimed to understand farmers’ management decisions to cope with weather variability and related consequences. We used a case study approach to analyse temporal interactions between farming system components using data collected over three consecutive years (2017–2019). We focused on three research questions. First, how do farmers navigate the regular patterns of seasonal variations in rainfall, prices, food and fodder availability, and income? Second, how does seasonality influence complementarity between farm components, and trade-offs and synergies among farming objectives that result from the allocation of scarce resources? Finally, how do farming households of different resource endowments respond to unexpected changes and how does this affect the above-mentioned synergies and trade-offs? The data collection methods included (1) focus group discussions, (2) household surveys, and (3) detailed farm monitoring. Farmers undertook diverse production activities, which helped to mitigate negative consequences of crop failure. While providing opportunities for increased adaptive capacity, this diversity also creates interdependencies among farming system components, leading to reinforced positive outcomes in good years and negative outcomes in bad years. This double-edged sword challenges the simple assumption that diversification increases the stability of a farming system. All farm types faced seasonal resource constraints to adapt to unexpected changes. However, the magnitudes of changes in synergies and trade-offs among objectives were less pronounced for medium resource endowed farmers because of their more balanced people- and herd-to-land ratio compared to high resource endowed farmers. Our findings suggest that a better understanding of farm management decisions and the influence of seasonality is key to support farm productivity and to expand the adaptive capacity of smallholders. We suggest that policies aiming to support farm productivity should pay attention to the specific impediments faced by farms with different resource endowments to adapt to changes. Especially, access to credit helps poorer farmers not only to navigate the seasonal food and cash constraints but also to escape poverty traps.